Penerapan Metode Reader Response Criticism dalam Jemaat tentang Makna Ciptaan Baru dalam 2 Korintus 5:17 di Gereja Banua Niha Keriso Protestan (BNKP) Tobasa Balige - Yusni Mawati Hia (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The purpose of this study was to determine the meaning of the new creation in the reading of 2 Corinthians 5:17 through the understanding of the BNKP Tobasa congregation and how they interpret the spiritual change in their daily lives. The method used in this study is the reader response criticism method, which emphasizes the active role of the reader or congregation in shaping the understanding of the Bible text. This study involved eight members of the BNKP Tobasa Balige congregation as informants, consisting of various backgrounds and ages. Data collection was carried out through in-depth interviews to explore how each individual interprets the concept of the new creation as a change that includes the renewal of the heart, mindset, and attitude of life guided by the Holy Spirit. They view the new creation as a process of transformation that brings someone out of an old life full of sin to a new life in Christ. However, even though there is a good theological understanding, it was also found that there is still a gap between understanding and application in daily life. Some congregations have not fully displayed the character and behavior that reflect life as a new creation both in relationships between fellow congregations and in their attitudes towards life of faith. This emphasizes the importance of ongoing formation in the congregation, especially to deepen their understanding of the meaning of the new creation and how it should be realized in real action.